2021
DOI: 10.2196/30350
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Mobile Game for Culturally Sensitive Child Sexual Abuse Prevention Education in Tanzania: Mixed Methods Study

Abstract: Background Globally, 3 out of 20 children experience sexual abuse before the age of 18 years. Educating children about sexual abuse and prevention is an evidence-based strategy that is recommended for ending child sexual abuse. Digital games are increasingly being used to influence healthy behaviors in children and could be an efficient and friendly approach to educating children about sexual abuse prevention. However, little is known on the best way to develop a culturally sensitive game that targ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Therefore, the evidence remains scarce with respect to the compatibility of AI-driven serious games with the sociocultural practices of consumers playing them. Literature indicates that understanding a community’s sociocultural practices can significantly contribute toward designing and building reliable serious games; hence, more studies in the reported countries, as well as others, are needed [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the evidence remains scarce with respect to the compatibility of AI-driven serious games with the sociocultural practices of consumers playing them. Literature indicates that understanding a community’s sociocultural practices can significantly contribute toward designing and building reliable serious games; hence, more studies in the reported countries, as well as others, are needed [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning child abuse prevention, most studies have been conducted to prevent child sexual abuse using SGs [20,[25][26][27][28][29]. Additionally, Love et al (2016) examined the feasibility of gamification-based parenting programs to help in preventing child abuse [15].…”
Section: Discussionmentioning
confidence: 99%
“…SG is defined as any game that is used for purposes other than entertainment, such as education, prevention, and treatment, as well as, gamification was developed to "the use of game design elements within non-game contexts" [17,18]. Studies have shown applications of these technologies in the management of child abuse [15,[19][20][21]. For instance, Malamsha et al (2021) have developed a mobile-based SG to prevent child sexual abuse (CSA) based on the sociocultural context of Tanzania [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, although there is extensive literature on child maltreatment, child abuse and neglect, and prevention efforts, only a tiny proportion of the strategies adopted to prevent and combat child abuse and neglect deal with the use of technology (e.g., Baggett et al 2017, Fujiwara et al 2020, Guastaferro, 2016, Gülırmak and Orak 2020, Hamilton-Giachritsis et al 2018, Kang et al 2020, Lefever et al 2017, Malamsha et al 2021, Mast et al 2014, Ondersma et al 2017, Schein et al 2022. However, there is no scoping review study evaluating the use of technology tools for the prevention of child abuse and neglect in the literature.…”
Section: Introductionmentioning
confidence: 99%